Trusted from Home: Managerial Beliefs and Workers' Spatial Autonomy - Adam Gill; Oskar Nordström Skans (Institute of Labor Economics (IZA), 2024)
A key difference between on-site and remote work is the reduction in direct managerial oversight when tasks are performed outside traditional office settings. We use survey data on manager trust—measured by the question "...do you think that most people would try to take advantage of you if they got the chance?"—and relate the answers to employees' work-from-home intensities. Our results show that the remote work intensity is higher in countries, regions, and regions-by-industries where managers have higher levels of trust. This association remains robust after controlling for other dimensions of societal trust and confounding factors such as occupation types, broadband access, and digital skills. Manager trust was strongly related to work-from-home levels before the pandemic, and the association became even stronger for occupations in the middle of the remote work distribution following the pandemic surge in work from home. Overall, our findings suggest that manager trust is a crucial prerequisite for high sustained levels of remote work.
Keywords: J32; M54; D83; 330; work from home; remote work; management; trust; shirking